Planet Forex Currency Trading in the Digital Age - Cofnas, Abe (Springer International Publishing, 2018)
This valuable book provides a much-needed integration of fundamental analysis of global forces and technical analysis to provide highly probable trades in currency markets. Fundamental analysis is often too vague and not quantified. This book provides insights into fundamental analysis and then calibrates it to trading strategies and techniques. Fundamentals are clearly defined as longer-term economic expectations regarding growth, inflation, and labor conditions. Nearer-term understanding of fundamentals deals with market psychology, where markets are manifest risk-on and risk-off emotions. Currencies are explained as expectations battles generating expectation waves. With real trading examples included to underscore the concepts, Planet Forex gives readers an invaluable primer on trading market sentiment that is unprecedented. This book is a must-read for global forex traders, portfolio managers, and other employees in the forex industry, including exchanges, brokerage firms, and financial planners and advisors.